Self Efficacy Pasien Diabetes Melitus dalam Pengelolaan Makan di UPTD Puskesmas Kecamatan Sananwetan Kota Blitar - Rizha Malayanita (Journal of Ners and Midwifery, 2017)
Self efficacy in meal management of diabetic patients, which is one of the self regulating ability of individuals in meal management of diabetic patients. The purpose  of this research to determine self efficacy in meal management of patients with diabetes mellitus such amount of food, type of food and eating schedules that consumed DM patients in Distict Health Sananwetan, Blitar. This research  used a descriptive design. The study population was all of DM patient who check their health at health centers Sananwetan, Blitar, and the  sample take  of 30 people with accidental sampling technique. The data collection is done by questionnaire closed-ended multiple choice questions. Collection data is done on the date June 6 until 18, 2016. The results showed that self efficacy in meal management of diabetic patients  is 50 % (15 people) less , 33.3 % (10 people) enough and 16.7 % (5 people) good. Patients with diabetes mellitus in district health Sananwetan Blitar ,need motivation , guidance and health education  to improve self efficacy meal management is good and right.